Molecular systematics and morphological identification of the cryptic species of the genus Acalles Schoenherr, 1825, with descriptions of new species (Coleoptera: Curculionidae: Cryptorhynchinae) - Schütte, André; Stüben, Peter E. (Zootaxa, 2015)
Molecular systematics and morphological study of the monophyletic weevil genus Acalles Schoenherr, 1825 are presented. Based on the mitochondrial CO1 barcoding gene and 16S ribosomal RNA gene, we discuss three difficult species complexes in the framework of a molecular phylogenetic reconstruction of 37 of 47 Western Palaearctic Acalles species or subspecies: the A. echinatus, A. maraoensis and A. sierrae complexes. Two results are given: 1. An exclusive focus on morphological, exoskeletal methods reach their limits in the case of many cryptic Cryptorhynchinae. In these cases molecular analysis is indispensable to resolve species level questions. 2. By using a combination of phenotypic and genotypic characters it is not only possible to ascertain phylogenetic relationships, but also to uncover new morphological, non-intraspecifical characteristics. Digital photography with image stacking makes this possible: for the first time we present photo key for Acalles species, a reliable, less costly and quick method for identification alongside DNA barcoding. The following taxonomic changes are given: Coloracalles edoughensis Desbrochers, 1892 comb. nov. (formerly Acalles edoughensis) from North Africa and Spain change to Coloracalles Astrin & Stüben, 2008 and Pseudodichromacalles xerampelinus Wollaston, 1864 comb. nov. from the Canarian Island Tenerife, Acalles bazaensis Stüben, 2001 syn. nov. is a junior synonym of Acalles sierrae H. Brisout, 1865. Two new species of Acalles s. str. , A. iblanensis Stüben sp. nov. from Morocco and A. vorsti Stüben sp. nov. from Spain (Mallorca), and a new species of the subgenus Origoacalles Stüben & Astrin 2010, A. granulimaculosus Stüben sp. nov. from La Gomera, are described. Acalles temperei Péricart, 1987 stat. nov. is a subspecies of A. parvulus Boheman, 1837. A catalogue of all 43 (+4 incertae sedis) species of Acalles is presented. Finally and for the first time we compare 9 of 12 known North American so-called “Acalles” species with the Western Palaearctic species of Acalles surrounding the type species Curculio camelus Fabricius, 1792. The morphological and molecular analysis for the New World Acalles show that none of the species from the United States actually belong to the genus Acalles or one of the other genera of Western Palaearctic Cryptorhynchinae. There is one exception: Acalles costifer Le Conte, 1884, is transferred to the phylogenetically basal genus Acallocrates Reitter, 1913 as Acallocrates costifer (LeConte, 1884) comb. nov.